Oxidative Phosphorylation as an Emerging Target in Cancer Therapy - Ashton, Thomas M; McKenna, W Gillies; Kunz-Schughart, Leoni A; Higgins, Geoff S (Clinical cancer research, 2018)
Cancer cells have upregulated glycolysis compared with normal cells, which has led many to the assumption that oxidative phosphorylation (OXPHOS) is downregulated in all cancers. However, recent studies have shown that OXPHOS can be also upregulated in certain cancers, including leukemias, lymphomas, pancreatic ductal adenocarcinoma, high OXPHOS subtype melanoma, and endometrial carcinoma, and that this can occur even in the face of active glycolysis. OXPHOS inhibitors could therefore be used to target cancer subtypes in which OXPHOS is upregulated and to alleviate therapeutically adverse tumor hypoxia. Several drugs including metformin, atovaquone, and arsenic trioxide are used clinically for non-oncologic indications, but emerging data demonstrate their potential use as OXPHOS inhibitors. We highlight novel applications of OXPHOS inhibitors with a suitable therapeutic index to target cancer cell metabolism. .